PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP TAX AVOIDANCE - Meila Sari; Heidy Paramitha Devi (Universitas PGRI Madiun, 2018)
This study aims to determine the effect of corporate governance and profitability to tax avoidance. Tax avoidance in this study is measured by Cash Effective Tax Rate. His study used a sample of mining companies listed on the Indonesia Stock Exchange during 2010-2015 using purposive sampling method. The method of analysis used is multiple regression analysis. The results of this study indicate that the proxy of corporate governance namely institutional ownership and independent board of commissioner influence tax avoidance. The results also show that tax avoidance is not influenced by the audit committee and audit quality. The results of profitability studies proxied with Return on Assets show that profitability affects tax avoidance.Keywords: cash effective tax rate corporate governance, profitability, and tax avoidance.